Intelligent agent concepts in information centers / Mazwani Ayu Mazlan, Jannatul Iza Ahmad Kamal and Intan Nurbaizura Zainuddin - Mazlan, Mazwani Ayu; Ahmad Kamal, Jannatul Iza; Zainuddin, Intan Nurbaizura (Research Management Institute (RMI), 2014)
Human workforce is an important part of community economic development in any economic climate, and certainly even more critical during the financial crises we 're experiencing today. This has come to describe a relatively wide range of activities, policies and programs employed by geographers to create, sustain and retain a viable workforce that can support current and future businesses and industry. It is a systematic process for identifying the human resources required to meet organizational goals and developing strategies to meet those requirements. Intelligent agent helps in facilitating the storage and retrieval of information as a result of the activities of the institution which involves a process of managing and maintaining information. Thus, the objectives of this paper are to examine the intelligent agent solution and to identify the effective usage of intelligent agents in information centres, and to describe the four types of intelligent agents adopted by these information centres.